ANALISIS BIBLIOMETRIK MENGGUNAKAN VOSVIEWER DARI PUBLIKASI TENTANG SISTEM ANTRIAN - Muh. Taufiq (2023)
The current publication of scientific publications shows an increase in the number of publications each year which illustrates that the development of the repertoire of a field of study is increasing. Researchers in this case analyze publications related to the queuing system. These developments can be analyzed using bibliometric techniques which serve as evaluation material to assess a study that will be made by future researchers. This study aims to determine the map of research developments related to the queuing system from 2012-2022, identify development maps based on keywords, and researcher productivity. The database used by researchers is document data from Scopus for publication of queuing systems. The data will be analyzed using the VOSviewer application to produce a bibliometric visualization of the prohibited system data publication. A study of publications related to queuing systems from 2012 - 2022 shows an increasing trend every year. China is the most prolific country to issue publications related to queuing systems. Analysis of the performance and effectiveness of the queue model that is currently running has been the focus of attention of previous researchers. The most relevant sources for further research can refer to IEEE Transactions on Parallel and Distributed Systems, Nucleic Acids Research, Transportation Research Part C: Emerging Technologies, IEEE Transactions on Computers, and International Journal of Communication Systems. Kumar R. is the most prolific author while the most collaborations are Sztrik J. and Nazarov A..